Study of acceptability, efficacy and side effects of non-steroidal contraceptive ormeloxifene and its comparative evaluation with combined oral contraceptives - Gupta, Neena; Siddiqui, Eram; Dwivedi, Divya; Jahan, Uruj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Despite their efficacy, COCs are associated with various side effects, including mood changes, weight gain, and cardiovascular risks, which can limit their acceptability among some women. These challenges have prompted ongoing research into alternative contraceptive methods that offer effective pregnancy prevention while mitigating hormonal side effects. In this context we conducted a study to assess the acceptability, effectiveness, and side effects of the non-steroidal contraceptive ormeloxifene for contraception, and to compare it with combined oral contraceptives (COCs). Methods: The study was a prospective longitudinal study carried out in the department of obstetrics and gynecology (UISEMH), GSVM medical college, Kanpur, Uttar Pradesh, India. Results: The study included two groups: 90 women opted for ormeloxifene (postpartum, post-abortal, and interval cases) as their contraceptive method, while another 53 women chose combined oral contraceptives (post-abortal and interval cases). The majority of participants in both groups were aged between 26 and 30 years. Patients were monitored for one year, with assessments conducted at the 3rd, 6th, and 12th months following initiation of the oral pills, and no participants were lost to follow-up. The study found statistically significant differences, particularly noting an 85.5% continuation rate with ormeloxifene, which was markedly higher compared to 39.6% observed with COCs. Conclusions: Ormeloxifene is a safe non-steroidal contraceptive option for pregnancy spacing and demonstrates comparable acceptability to COCs. Side effects beyond menstrual issues (such as weight gain, nausea, vomiting, and headache) are the primary reasons for discontinuation of COCs. Both hormonal (combined oral contraceptives) and non-hormonal (ormeloxifene) oral contraceptive pills are safe and effective methods of contraception.